2008
DOI: 10.1111/j.1365-2869.2008.00654.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dextroamphetamine, caffeine and modafinil on psychomotor vigilance test performance after 44 h of continuous wakefulness

Abstract: Summary Prolonged sleep loss impairs alertness, vigilance and some higher‐order cognitive and affective capacities. Some deficits can be temporarily reversed by stimulant medications including caffeine, dextroamphetamine, and modafinil. To date, only one study has directly compared the effectiveness of these three compounds and specified the doses at which all were equally effective in restoring alertness and vigilance following 64 h of wakefulness. The present study compared the effectiveness of these same th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
68
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(76 citation statements)
references
References 42 publications
(97 reference statements)
7
68
0
1
Order By: Relevance
“…However, it may be possible that similarly representing U as a monotonic function of sleep debt could simultaneously account for the increased impairments during higher sleep debts and decreased impairments during lower sleep debts, thereby better (Table 1) in study V6. 17 Thin dotted vertical line denotes caffeine intake (d1 = 600 mg). Other descriptors are identical to those in Figure 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it may be possible that similarly representing U as a monotonic function of sleep debt could simultaneously account for the increased impairments during higher sleep debts and decreased impairments during lower sleep debts, thereby better (Table 1) in study V6. 17 Thin dotted vertical line denotes caffeine intake (d1 = 600 mg). Other descriptors are identical to those in Figure 1.…”
Section: Discussionmentioning
confidence: 99%
“…17 The TSD phase was preceded by one night of 8 h TIB (baseline) and followed by one night of 12 h TIB (recovery). All subjects performed a 5-min PVT every 2 h throughout their time awake.…”
Section: Study V6mentioning
confidence: 99%
“…10,37 Higher daily caffeine intake of soldiers in combat units (J-MHAT 8) was also associated with disrupted sleep following night operations, which is consistent with the effect of caffeine on recovery sleep following its use to maintain cognitive function during an overnight period of sustained wakefulness. 19,20,38,39 Clearly, obtaining sufficient sleep would be the preferred option but if this is not possible, due to the demands of combat, then use of caffeine to counter the effects of sleep loss is one strategy consistently documented by studies conducted in various military training scenarios. 11,[15][16][17]36 An alternative explanation, suggested by Toblin et al, 25 is greater caffeine intake impacts the quality of sleep, thereby increasing daytime sleepiness and subsequent accidents.…”
Section: Nutritional Neuroscience 2018mentioning
confidence: 99%
“…Participants were allowed to sleep at 20:00 Saturday evening (Day 3) until 08:00 the placebo group (P < 0.01). Interestingly, there was no significant difference among the groups with regard to the average pick-up time for each ring, F (3,38) = 0.93, P = 0.963, suggesting that these effects were not due simply to faster processing or motor speed. When the TOH was re-administered following a full night of recovery sleep, no drug group differences were apparent for total moves or for average pick-up times.…”
Section: Subjective Sleepinessmentioning
confidence: 93%
“…The total number of moves and pick-up times were averaged across the 4 trials for each subject. There was a significant main effect of drug group on the average number of moves to solve the puzzle across the 4 trials, F (3,38) = 3.20, P = 0.034 (see Figure 2). Tukey post hoc comparisons showed that the caffeine group solved the TOH 5-ring task with significantly (P < 0.01) fewer moves than either the placebo, dextroamphetamine, or modafinil groups (Figure 3).…”
Section: Tower Of Hanoimentioning
confidence: 98%